Generation of two induced pluripotent stem cell lines from dilated cardiomyopathy patients carrying TTN mutations - Tina Tianbo Zhang; Shane Rui Zhao; Christina Alamana; Mengcheng Shen; Victoria Parikh; Matthew T. Wheeler; Joseph C. Wu (Stem Cell Research, 2022)
Dilated cardiomyopathy (DCM) is a common heart disease that can lead to heart failure and sudden cardiac death. Mutations in the TTN gene are the most frequent cause of DCM. Here, we generated two human induced pluripotent stem cell (iPSC) lines from the peripheral blood mononuclear cells (PBMCs) of two DCM patients carrying c.94816C>T and c.104188A>G mutations in TTN, respectively. The two lines exhibited a normal morphology, full expression of pluripotency markers, a normal karyotype and the ability of trilineage differentiation. The two lines can serve as useful tools for drug screening and mechanism studies on DCM.